El aporte de la danza oriental en el proceso de convertirse en persona de Carl Rogers en mujeres participantes de la academia Shanti Yoga estudio de Quito, en el periodo enero 2012 a enero 2013 - Ayuquina Sánchez, Maribel Fernanda (2014)
Man is nowadays living multiple new stressing situations. Living this world, is under pressure, acting and assuming unaccepted roles and duties. Persons and societies are bound to a deep cultural crisis triggering up mental and physical distress. We look now for new alternatives for a better and healthy living.Bellydance is definitely, we believe, a good answer to this social problem. Backing up our hypothesis, we focused on the experience of a group of young woman in the Shanti yoga Studio in Quito, Ecuador. There we took a Clinical Psychology approach, to point out the benefits of their dance practice for the personal growth, change and development. Deepening our research, we assume Carl Rogers’ ideas about the process of becoming a person and bioenergy concepts from Wilhem Reich and Alexander Lowen. A we state with them the close relationship between our body and our emotions. If they are right, we come to the conclusion that our body through bellydance practice helps us to process better our inner conflicts, widens our self-knowledge that leads us to a close experience of a our real and authentic self . In our field work, we asked our dance group to take Sacks and Espinosa test to explore their self-knowledge area and, the in a personal and detailed interview, they processed with our help. Their dance practice in relation with their personal development. Ending up our work, we come to some conclusions and thereby we pretend to encourage those who dare thinking through bellydance.